Centralizers and Double Centralizers for Prime and Semiprime -rings: - Khuder, Aya Hussein; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2024)
The purpose of this paper is to discuss the centralizers and the double centralizers in prime and semiprime rings with fulfilling certain identities.